Quality of life after hip fracture: a 12-month prospective study - Francisco Javier Amarilla-Donoso; Raul Roncero-Martin; Jesus Maria Lavado-Garcia; Rosaura Toribio-Felipe; Jose Maria Moran-Garcia; Fidel Lopez-Espuela (PeerJ, 2020)
Background Hip fracture is an important and frequent health problem worldwide. To date, there are still limited studies focused on the analysis of health-related quality of life (HRQOL) after a hip fracture in the Spanish population, especially with long-term follow-up. Objective To determine the HRQOL at 12 months after hip fracture and to identify potential factors associated with HRQOL. Design Prospective observational study. Setting Traumatology units of two university hospitals in province Cáceres (Spain). Participants A total of 224 patients were admitted to the unit and required immediate surgery due to a hip fracture. Methods HRQOL was measured with the EuroQol-5D questionnaire (EQ-5D) and the SF-12 Health Survey. Results Scores from the visual analog scale EQ-5D decreased significantly (p < 0.001) from 72.8 at baseline to 48.3 after 1 month, to 48.2 after 6 months and to 46.1 after 12 months. The EQ-5D index score showed a similar significant reduction (p < 0.001) from 0.6 to 0.1, 0.3 and 0.3, respectively. Values of the physical component summary (PCS-12) significantly decreased (p < 0.001) from 38.6 at baseline to 31.0, 33.1 and 33.5. The mental component summary (MCS-12) decreased from 46.5 to 44.8 after 6 months (p = 0.022) and 44.3 after 12 months (p = 0.005). Factors potentially associated with HRQOL at 12 months after hip fracture were depression status after 12 months (B = 0–1.876; 95% CI [−2.409 to −1.343]; p < 0.001), functional ambulation classification after 12 months (B = −12.133; 95% CI [−17.970 to −6.297]; p < 0.001), EQ-5D VAS at baseline (B = 0.223; 95% CI [0.115–0.330]; p < 0.001), and age (B = −0.323; 95% CI [−0.594 to −0.053; p = 0.015). Conclusions Patients experience a significant impairment in HRQOL H after a hip fracture, especially in self-care, pain/discomfort, usual activities, mobility and anxiety/depression. The decline in the HRQOL is effective the first month and lasts at least 12 months after the surgical intervention.